Outcomes of Endovascular Therapy With the Controlled Antegrade Retrograde Subintimal Tracking (CART) or Reverse CART Technique for Long Infrainguinal Occlusions. (April 2016) - Chou, Hsin-Hua; Huang, Hsuan-Li; Hsieh, Chien-An; Jang, Shih-Jung; Cheng, Shih-Tsung; Tsai, Sou-Chan; Wu, Tien-Yu; Ko, Yu-Lin
Purpose: To compare the safety, efficacy, and clinical outcomes associated with the controlled antegrade retrograde subintimal tracking (CART) or reverse CART (r-CART) technique to the conventional retrograde approach in the treatment of patients with long infrainguinal occlusions.Methods: From May 2008 to April 2014, 121 patients failed antegrade recanalization and underwent a retrograde approach to recanalize long infrainguinal occlusions. Patients who underwent successful endovascular therapy (EVT) by the conventional retrograde approach (CRA group) were compared to patients who had successful EVT using the CART/r-CART technique (CART group) after failure of a bidirectional approach. The efficacy, safety, vessel patency, and other clinical outcomes were compared between the groups.Results: Fifty-eight patients (mean age 71.6±12.2 years; 32 men) underwent successful EVT (47.9%, 58/121) using the conventional retrograde approach (CRA group), while 44 patients (mean age 70.8±11.1 years; 31 men) among the 50 patients who underwent the CART/r-CART technique were successfully treated (88.0%, 44/50). Both groups had similar average occlusion lengths and gained 100% immediate hemodynamic success after EVT. There was no significant difference between the groups regarding procedure-related complications. During follow-up, 28 patients died (p=0.380), but there were no differences in the rates of major (p=0.279) or minor amputation (p=0.417) between the groups. There was no difference in the 2-year primary patency (31% vs 24%, p=0.686), assisted primary patency (66% vs 76%, p=0.251), target vessel revascularization (65% vs 54%, p=0.845), or sustained clinical success (52% vs 46%, p=0.995) rates between the CRA and CART groups, respectively.Conclusion: Based on acceptable safety, efficacy, and follow-up results in this study, the CART/r-CART technique can salvage patients with long peripheral occlusions after failure of the conventional antegrade or retrograde approach.